Building a better workforce: A case study in management simulations and experiential learning in the construction industry. Issue 1 (9th January 2017) - Douglas-Lenders, Rachel Claire; Holland, Peter Jeffrey; Allen, Belinda
Abstract : Purpose: The purpose of this paper is to examine the impact of experiential simulation-based learning of employee self-efficacy. Design/methodology/approach: The research approach is an exploratory case study of a group of trainees from the same organisation. Using a quasi-experiment, one group, pre-test-post-test design (Tharenou et al., 2007), a questionnaire with validated scales at Time 1 (T1) prior to training and Time (T2) three months after training were used. All scales had been validated by the researchers and had acceptable levels of reliability. In addition interviews are undertaken with the participants immediately at the end of the programme. Findings: The research found strong evidence of the positive impact of the training on skills transfer to the workplace with support from supervisors as key criteria. Research limitations/implications: There remains a need for additional studies with larger and more diverse samples and studies which incorporate control groups into their design. Practical implications: This study provided support for the transfer of knowledge using simulation-based training and advances our limited knowledge and understanding of simulation-based training as a form of experiential (management) learning and development. Originality/value: This is the first study to undertake a longitudinal analysis of the impact on self-efficacy in the workplace and as such adds to the research in this field.